1992
DOI: 10.1037/h0101254
|View full text |Cite
|
Sign up to set email alerts
|

A review of attempts to integrate spiritual and standard psychotherapy techniques.

Abstract: This is a review of attempts to integrate psychotherapeutic techniques derived from religious/spiritual and secular psychological perspectives including findings from the cognitive-behavioral, psychodynamic, existential-humanistic, and health psychology areas. While research evidence is not abundant, traditional approaches are being applied to spiritual concerns, and spiritual thought is being extended into clinical domains. Caveats abound, but on the whole, commonalities are plentiful and rapprochement is evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Furthermore, the recent growth of the number of adherents to Islam within the African American community provides an excellent opportunity to investigate religious counseling with people who are not Christian or Jewish or to compare Christian, Muslim, and nonreligious clients' responses to counseling. Payne et al (1992) summarized religious adaptations of cognitive-behavioral, psychodynamic, existential-humanistic, and health psychology programs; however, they reviewed little empirical research. Most theoretical integration has combined Protestant Christianity and some approach to counseling.…”
Section: (Text Continues On Page 474)mentioning
confidence: 99%
“…Furthermore, the recent growth of the number of adherents to Islam within the African American community provides an excellent opportunity to investigate religious counseling with people who are not Christian or Jewish or to compare Christian, Muslim, and nonreligious clients' responses to counseling. Payne et al (1992) summarized religious adaptations of cognitive-behavioral, psychodynamic, existential-humanistic, and health psychology programs; however, they reviewed little empirical research. Most theoretical integration has combined Protestant Christianity and some approach to counseling.…”
Section: (Text Continues On Page 474)mentioning
confidence: 99%
“…There is now considerable empirical evidence that spiritual practices promote physical and emotional healing (Benson, 1996;Borysenko & Borysenko, 1994). Several studies have also shown that psychotherapy with religious clients that includes spiritual interventions in the treatment package is as effective, and sometimes more effective, than standard secular treatments (Payne, Bergin, & Loftus, 1992;Worthington et al, 1996).…”
Section: General Considerations In Using Spiritual Interventionsmentioning
confidence: 99%
“…Sowders (2001) found no significant interactions between participants' extrinsic or intrinsic religious orientation and the preference for a therapist's usage of a religious or a nonreligious counseling approach. Both these findings support the possibility that respect for the client's religious beliefs may be more important than the religious matching of therapists and clients (Kelly, 1995;Mayers et al, 2007;Payne, Bergin, & Loftus, 1992;Richards & Bergin, 1997;Stolovy et al, 2013). For example, Kelly et al (1996) found that 43.8% of Muslim clients did not prefer either a Muslim or a non-Muslim therapist, provided that non-Muslim therapists have an understanding of Islamic values.…”
Section: Discussionmentioning
confidence: 64%